Pneumonia by Listeria monocytogenes: A Common Infection by an Uncommon Pathogen - Theocharis Koufakis; Marianneta Chatzopoulou; Anastasios Margaritis; Maria Tsiakalou; Ioannis Gabranis (Case Reports in Infectious Diseases)
Infections by Listeria monocytogenes typically occur in infants, the elderly, pregnant women, and immunosuppressed subjects. Pulmonary infections in adults are extremely uncommon and only few reports can be found in the literature. We here report a case of Listeria pneumonia in an 85-year-old female patient and we discuss our diagnostic and therapeutic approach. Despite being rare and in most cases difficult to be identified, Listeria pneumonia should always be considered in immunosuppressed patients, presenting with fever and symptoms from the lower respiratory system.